Pemanfaatan Desain Grafis dalam Pembuatan Iklan Digital untuk Meningkatkan Brand Awareness di SMK Media Informatika - Raffa Nurprasetyo Araya; Indra Bagoes Muafa; Firmansyah; Athila Defian Rizkimu; Ahmad Taher (PT Jurnal Cendekia Indonesia, 2025)
The continuous development of digital technology has significantly influenced how educational institutions present and promote their identity. One proven strategy is the application of graphic design in developing digital advertisements to strengthen brandawareness. This Community Engagement (PKM) initiative was designed to enhance the knowledge and technical abilities of students at SMK Media Informatika, especially those majoring in Multimedia, in producing compelling and effective digital advertisements. The implementation involved visual design workshops, hands-on promotional content creation, and assessment of student projects. The outcome of this programindicated a notable improvement in students' skills in applying design principles and in their understanding of the role of visual identity in educational promotion. Moreover, the activity fostered student engagement in creatively representing their school through digital platforms. This initiative is expected to serve as a replicable model for empowering students in digital promotional practices at other educational institutions.